2015
DOI: 10.18632/oncotarget.3113
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin promotes a cancer stem cell-like phenotype in hepatocellular carcinoma cells via an integrin-NF-κB–HIF-1α pathway

Abstract: There is increasing evidence to suggest that hepatocellular carcinomas (HCCs) are sustained by a distinct subpopulation of self-renewing cells known as cancer stem cells. However, the precise signals required for maintenance of stemness-like properties of these cells are yet to be elucidated. Here, we demonstrated that the level of oncoprotein osteopontin (OPN) in tumor cells of the edge of bulk tumors was significantly correlated with the clinical prognosis of patients with HCC. OPN was highly expressed in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 47 publications
3
65
0
1
Order By: Relevance
“…Nevertheless, information is lacking on the relationship between matrix stiffness stimuli and HCC stem characteristic. Lately, OPN is found to promote a cancer stem cell-like phenotype in HCC cells via an integrin NF-κB-HIF-1α pathway [61]. Intriguingly, our previous data also suggested that higher matrix stiffness upregulated OPN expression in HCC cells [17], which implies a linkage between matrix stiffness and HCC stemness.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, information is lacking on the relationship between matrix stiffness stimuli and HCC stem characteristic. Lately, OPN is found to promote a cancer stem cell-like phenotype in HCC cells via an integrin NF-κB-HIF-1α pathway [61]. Intriguingly, our previous data also suggested that higher matrix stiffness upregulated OPN expression in HCC cells [17], which implies a linkage between matrix stiffness and HCC stemness.…”
Section: Discussionmentioning
confidence: 97%
“…3,4). However, several recent reports highlight their importance for stem-like properties, while the role of EGFR in this regard is less clear (4650). Osteopontin is an upstream activator of Src and EGFR signaling (38, 47, 51).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that ERRα, combined with PGC1α, activates the promoter of osteopontin (OPN) gene and leads to elevated OPN expression in CRC cells (29). OPN is a glycoprotein secreted by a variety of tissues and enhances cancer stem cell phenotypes in various cancer types (30,31). Higher levels of OPN are produced by macrophages when co-cultured with cluster of differentiation 44-positive CRC stem cells, subsequently increasing the tumorigenicity of the CRC cells (32).…”
Section: Errα Expression (N=128) ------------------------------------mentioning
confidence: 99%